Combination of Vitamin C and Curcumin Safeguards Against Methotrexate-Induced Acute Liver Injury in Mice by Synergistic Antioxidant Effects - Hasan Khudhair, Dhekra; Al-Gareeb, Ali I.; Al-kuraishy, Hayder M.; El-Kadem, Aya H.; Elekhnawy, Engy; Negm, Walaa A.; Saber, Sameh; Cavalu, Simona; Tirla, Adrian; Alotaibi, Saqer S.; Batiha, Gaber El-Saber (Frontiers in Medicine, 2022)
Methotrexate (MTX), an antineoplastic and immunosuppressive drug, widely used in the treatment of different types of cancers and the management of chronic inflammatory diseases. However, its use is associated with hepatotoxicity. Vitamin C (VC) and curcumin (CUR) exhibit anti-inflammatory and antioxidant effects. Thus, we aimed to investigate the potential hepatoprotective effects of VC and CUR pretreatment alone and in combination against MTX-induced hepatotoxicity. Albino mice were randomly divided into 7 groups: the control group, which received only normal saline; MTX group; VC group, pretreated with VC (100 or 200 mg/kg/day orally) for 10 days; CUR group, pretreated with CUR (10 or 20 mg/kg/day orally); and combination group, which received VC (100 mg/kg) and CUR (10 mg/kg). MTX was administered (20 mg/kg, intraperitoneally) to all the groups on the tenth day to induce hepatotoxicity. Forty eight hours after MTX administration, the mice were anesthetized. Blood samples were collected, the liver was removed for biochemical analysis, and a part of the tissue was preserved in formalin for histopathological analysis. The results indicated that pretreatment with a combination of VC and CUR induced a more significant decrease in the serum levels of alanine transaminase, aspartate transaminase, alkaline phosphatase, and lactic dehydrogenase and a significant increase in the tissue level of superoxide dismutase and glutathione; furthermore, it induced a significant decrease in malondialdehyde levels and improvement in histopathological changes in the liver tissues, confirming the potential hepatoprotective effects of the combination therapy on MTX-induced liver injury. To conclude, MTX-induced hepatotoxicity is mediated by induction of oxidative stress as evident by increased lipid peroxidation and reduction of antioxidant enzyme activity. Pretreatment with VC, CUR or their combination reduces the MTX-induced hepatotoxicity by antioxidant and anti-inflammatory effects. However, the combined effect of VC and CUR provided a synergistic hepatoprotective effect that surpasses pretreatment with CUR alone but seems to be similar to that of VC 200 mg/kg/day. Therefore, VC and CUR combination or a large dose of VC could be effective against MTX-induced hepatotoxicity. In this regard, further studies are warranted to confirm the combined hepatoprotective effect of VC and CUR against MTX-induced hepatotoxicity.